1997
DOI: 10.1128/aem.63.5.1661-1666.1997
|View full text |Cite
|
Sign up to set email alerts
|

ord1, an oxidoreductase gene responsible for conversion of O-methylsterigmatocystin to aflatoxin in Aspergillus flavus

Abstract: Among the enzymatic steps in the aflatoxin biosynthetic pathway, the conversion of O-methylsterigmatocystin to aflatoxin has been proposed to be catalyzed by an oxidoreductase. Transformants of Aspergillus flavus 649WAF2 containing a 3.3-kb genomic DNA fragment and the aflatoxin biosynthesis regulatory gene aflR converted exogenously supplied O-methylsterigmatocystin to aflatoxin B 1 . A gene, ord1, corresponding to a transcript of about 2 kb was identified within the 3.3-kb DNA fragment. The promoter region p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 36 publications
3
40
0
1
Order By: Relevance
“…The site is also absent in most of the genes that have been identified as part of the aflatoxin biosynthetic pathway, e.g. ord-1 from A. flavus (Prieto and Woloshuk, 1997) and ver-1 from A. parasiticus (Skory et al, 1992). The AnAflR binding site defined in this work, on the other hand, is found in the promoter regions of these genes and others for which sequences are available in the database.…”
Section: Discussionmentioning
confidence: 68%
“…The site is also absent in most of the genes that have been identified as part of the aflatoxin biosynthetic pathway, e.g. ord-1 from A. flavus (Prieto and Woloshuk, 1997) and ver-1 from A. parasiticus (Skory et al, 1992). The AnAflR binding site defined in this work, on the other hand, is found in the promoter regions of these genes and others for which sequences are available in the database.…”
Section: Discussionmentioning
confidence: 68%
“…This could partly be due to the sensitivity of the technique or weak signal intensity of the hybridizing clone on the macro-array nylon membrane. Previous authors have reported that cytochrome P450 monooxygenase may be involved in detoxification of plant-derived compounds or in the biosynthesis of secondary metabolites such as aflatoxin in Aspergillus flavus by an oxidoreductase gene ord1 [48]. The enzyme has been reported in several pathogenic and saprotrophic fungi, such as Heterobasidion annosum (P-type), Agaricus bisporus, Phanerochaete chrysosporium, Cercosporanzeae maydis and Nectria haematococca [24,43,[49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…1) [15]. The gene, ord1, responsible for this enzyme activity was mapped to a 3.3 kb genomic DNA fragment on cosmid 8B9 [15,40]. The product of ord1 is a cytochrome P450 monooxygenase which was assigned to a new cytochrome P450 family named CYP64.…”
Section: Sterigmatocystin To A£atoxinmentioning
confidence: 99%
“…The product of ord1 is a cytochrome P450 monooxygenase which was assigned to a new cytochrome P450 family named CYP64. Yeast expressing ord1 under the control of the Saccharomyces cerevisiae galactose-inducible gal1 promoter were able to convert OMST to AFB1, indicating that ord1 is suf-¢cient to accomplish the last step of the a£atoxin biosynthetic pathway [40]. In A. parasiticus, ordA was identi¢ed by chromosome walking, and this gene shares over 90 percent nucleotide sequence identity with ord1 (D. Bhatnagar, unpublished).…”
Section: Sterigmatocystin To A£atoxinmentioning
confidence: 99%